New species of the cleptoparasitic bee genus Stelis (Hymenoptera: Megachilidae, Anthidiini) from the Nearctic Region - Parker, Frank D.; Griswold, Terry (Zootaxa, 2013)
Descriptions and diagnoses of ten new Nearctic species of Stelis subgenus Stelis are presented: S. alta, S. anasazi, S. an-thocopae, S. broemelingi, S. imperialis, S. joanae, S. lamelliterga, S. occidentalis, S. paiute, and S. shoshone. Six of these species have been reared from trapnests. Host associations, all within the tribe Osmiini (Megachilidae), are provided.